Association of maternal oral health literacy with dental caries status of 6-9-year-old children according to the caries assessment spectrum and treatment (CAST) index - Mobina Marandi; Azadeh Babaei; Zahra Momeni (BMC Oral Health)
Abstract Objectives This study aimed to assess the association of maternal oral health literacy (OHL) with dental caries status of 6-9-year-old children according to the Caries Assessment Spectrum and Treatment (CAST) index. Methods This cross-sectional study evaluated 223 mothers and their 6-9-year-old children who were selected by convenience sampling. The OHL of the mothers was evaluated by the Oral Health Literacy-Adults Questionnaire (OHL-AQ) while the dental caries status of the children was assessed by the CAST index. Data were analyzed by the independent t-test, linear and logistic regression, and Spearman and Pearson’s correlation coefficients (alpha = 0.05). Results Of 223 children, 51.6% were males. The mean age of the children was 7.25 ± 1.02 years. Mothers with a higher educational level (P = 0.01) and socioeconomic status (P = 0.02) had higher OHL. Optimal oral health behavior of the mothers was significantly associated with their higher OHL, and a lower rate of caries in their children (P < 0.05). The mean OHL score of the mothers was 12.42 ± 2.78, and their OHL had a significant inverse association with primary molar (P < 0.00) and permanent first molar (P = 0.01) caries in their children. Also, the rate of primary molar (P = 0.01 and P = 0.00, respectively) and permanent first molar (P = 0.02 and P < 0.00, respectively) caries was significantly lower in children of working mothers, and those with a higher educational level. Conclusion The maternal OHL was significantly associated with the dental caries status of 6-9-year-old children according to the CAST index.